The increased expression of Piezo1 and Piezo2 ion channels in human and mouse bladder carcinoma - Etem, Ebru Onalan; Ceylan, Gulay Gulec; Ozaydin, Seda; Ceylan, Cavit; Ozercan, Ibrahim; Kuloglu, Tuncay (Wroclaw Medical Univ, 2018)
Background. Piezo1/2, a mechanically activated ion channel, is believed to play an important role in bladder carcinogenesis process. Piezo1/2 expression has not been previously reported in urinary bladder carcinoma, and little is known about its significance in bladder carcinogenesis. Objectives. In our study, we aimed to eva luate the Piezo1 and Piezo2 expression as developmental in mouse bladder tissue and bladder cancer tissue of mice and humans. Material and methods. The detection of developmental expression was performed on Po-P90 days in bladder tissue of Balb/c strain mice. Mice were divided into bladder cancer (n = 40) and control groups (n = 10). Bladder cancer in mice was created by using N-butyl-N-(4-hydroxybutyl)nitrosamine (BBN). In the study, 60 human subjects were included, whose normal tissues were used as controls. After the histopathological evaluation, the expression of Piezo1/2 genes was examined by reverse transcription polymerase chain reaction (RT-PCR) and immunohistochemistry in tumor and normal tissues. Results. In developmental period of the mice, Piezol expression increased on days 21 and 90, whereas Piezo2 expression increased on day 7 and decreased on day 90 in mouse bladder tissues. There was a significant increase in the expression of Piezo1/2 in both cancer groups compared to the control group. Piezo1 expression was significantly increased at tumor size, stage and grade. Piezo2 expression was upregulated in high grade tumors in human subjects. Conclusions. The developmental changes of Piezo expression on specific days demonstrate the role of these channels in bladder cancer development The dysfunction of Piezo1/2 expression may contribute to the carcinogenesis of bladder cancer by causing proliferative changes and angiogenesis. The expression of Rezo1/2 can provide new prognostic information for disease progression.
Keywords: bladder cancer; messenger RNA expression; Piezo channels